1999
DOI: 10.1007/pl00014152
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic sensory cortical responses evoked by tactile stimulations of the human face, oral cavity and flap reconstructions of the tongue

Abstract: Magnetoencephalography (MEG) is a procedure that analyzes the magnetic responses of neurons. An MEG system with a 37-channel superconductivity quantum interference device (SQUID) was used to record magnetic signals from the human brain in response to tactile stimulations of the face and oral cavity. Six normal individuals were studied as well as three patients who had undergone hemiglossectomies as treatment for carcinoma of the tongue and reconstruction with a pectoralis major myocutaneous flap. When the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…The present study found that the lip ECD was located higher than the tongue ECD of the SEFs, corresponding to the previous findings by cortical stimulation (Penfield and Boldrey 1937;Penfield and Rasmussen 1950), cortical recording of somatosensory potentials (McCarthy et al 1993), and SEFs (Yamashita et al 1999;Nakahara et al 2004). However, we found no statistical difference between the ECDs of the buccal gingiva, lingual gingiva, and tongue, in contrast to the previous conclusion by Penfield and colleagues (Penfield and Rasmussen 1950) that gingival SI is located higher than tongue SI, but which was based on complicated results.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found that the lip ECD was located higher than the tongue ECD of the SEFs, corresponding to the previous findings by cortical stimulation (Penfield and Boldrey 1937;Penfield and Rasmussen 1950), cortical recording of somatosensory potentials (McCarthy et al 1993), and SEFs (Yamashita et al 1999;Nakahara et al 2004). However, we found no statistical difference between the ECDs of the buccal gingiva, lingual gingiva, and tongue, in contrast to the previous conclusion by Penfield and colleagues (Penfield and Rasmussen 1950) that gingival SI is located higher than tongue SI, but which was based on complicated results.…”
Section: Discussionsupporting
confidence: 92%
“…The middle-latency component of tongue SEFs was also identified over both hemispheres at a peak latency ranging from 25 ms to 80 ms, with a posterior current orientation (Figure 2; Karhu et al, 1991; Nakamura et al, 1998; Yamashita et al, 1999; Disbrow et al, 2003; Nakahara et al, 2004; Maezawa et al, 2008, 2014a). Further investigation revealed that the initial and middle-latency components of tongue SEFs derived from the bilateral S1—specifically, the posterior bank of the central sulcus—although contralateral dominance was observed (Tamura et al, 2008).…”
Section: The Physiology Of Tongue Sensorimotor Processingmentioning
confidence: 94%
“…Since the SEFs for electrical tongue stimulation were first reported in the early 1990s (Karhu et al, 1991), several tongue SEF studies have been conducted using electrical (Nakahara et al, 2004; Maezawa et al, 2008; Sakamoto et al, 2008a) and mechanical stimulation (Nakamura et al, 1998; Yamashita et al, 1999; Disbrow et al, 2003; Tamura et al, 2008). …”
Section: The Physiology Of Tongue Sensorimotor Processingmentioning
confidence: 99%
“…These include: (a) clear geometry of the three divisions (ophthalmic-V1, maxillary-V2, mandibular-V3) of the face allows for measures of somatotopic representation to stimuli (Jensen et al, 1987;Capra and Dessem, 1992;Koyama et al, 1998;Yamashita et al, 1999); (b) it is possible to measure changes in brain activity using fMRI in the trigeminal ganglion (TG), and nucleus (spV), which is the equiv-alent of the dorsal horn in the spinal cord, as well as higher centers of the brain (e.g., ventromedial thalamus and somatosensory cortex) in the same subject; (c) the relatively large representation of the face in the somatosensory cortex compared with other areas of the body (Servos et al, 1999); and (d) the clinical populations within a disease group are relatively homogenous. Using fMRI, objective evaluation of treatment may be possible .…”
Section: Introductionmentioning
confidence: 99%